LAND-deFeND – An innovative database structure for landslides and floods and their consequences. (1st February 2018) - Napolitano, Elisabetta; Marchesini, Ivan; Salvati, Paola; Donnini, Marco; Bianchi, Cinzia; Guzzetti, Fausto
Abstract: Information on historical landslides and floods – collectively called "geo-hydrological hazards – is key to understand the complex dynamics of the events, to estimate the temporal and spatial frequency of damaging events, and to quantify their impact. A number of databases on geo-hydrological hazards and their consequences have been developed worldwide at different geographical and temporal scales. Of the few available database structures that can handle information on both landslides and floods some are outdated and others were not designed to store, organize, and manage information on single phenomena or on the type and monetary value of the damages and the remediation actions. Here, we present the LANDslides and Floods National Database (LAND-deFeND), a new database structure able to store, organize, and manage in a single digital structure spatial information collected from various sources with different accuracy. In designing LAND-deFeND, we defined four groups of entities, namely: nature-related, human-related, geospatial-related, and information-source-related entities that collectively can describe fully the geo-hydrological hazards and their consequences. In LAND-deFeND, the main entities are the nature-related entities, encompassing: (i) the "phenomenon", a single landslide or local inundation, (ii) the "event", which represent the ensemble of the inundations and/or landslides occurred in a conventional geographical area in a limited period, and (iii) the "trigger", which is the meteo-climatic or seismic cause (trigger) of the geo-hydrological hazards. LAND-deFeND maintains the relations between the nature-related entities and the human-related entities even where the information is missing partially. The physical model of the LAND-deFeND contains 32 tables, including nine input tables, 21 dictionary tables, and two association tables, and ten views, including specific views that make the database structure compliant with the EC INSPIRE and the Floods Directives. The LAND-deFeND database structure is open, and freely available fromhttp://geomorphology.irpi.cnr.it/tools . Highlights: Fundamental natural and human entities related to geo-hydrological hazard are defined. A database structure for non-homogeneous data on landslides and floods is proposed. EC directives on floods and geo-spatial data infrastructures are taken into account. Socio-economic data related to geo-hydrological hazards can be recorded in the DB. The structure localizes both the geo-hydrological hazards and their impacts.